Outdoor and indoor noise exposure : effect on university students' well-being in residential colleges / Muhammad Hafeez Fikhri Mohd Yussof and Norishahaini Mohamed Ishak - Mohd Yussof, Muhammad Hafeez Fikhri; Mohamed Ishak, Norishahaini (2018)
Noise is a result of human activities, such as urbanization, transportation development and industry. Despite the widespread of the noise, it has been treated differently than other pollutions. This research aims to determine noise levels and sources in college buildings at university. The objectives of this research are designed to assess the noise exposure levels experienced by students at a residential college building, find out the factors and recommend the solutions. To understand the source, and the degree of annoyance of the students due to the outdoor and indoor noise level, a total of 60 respondents were randomly selected from three residential colleges (Perindu, Teratai, and Delima) with 20 respondents each. The noise level measurement using the sound level meter in daytime and nighttime was adopted to find out the equivalent continuous level (LAeq) and traffic noise level (LA10) at the college area. Analysis showed that road vehicles are the major cause of noise nuisance that contributed 43% of the total respondents. The results for the outdoor and indoor noise level showed 10 dB increment from the permissible value of daytime and nighttime